What effect does exercise have on the immune system?. Issue 1 (January 2015) - Naumoff, Casey A.; Martin, Sean N.
Abstract : Evidence‐Based Answer : Regular exercise may decrease the frequency and severity of upper respiratory tract infections (URTI) (SOR: B, cohort studies).